Histopathological Effects of Omega-3 in Reducing Cartilage Destruction Progression in Mice with Knee Joint Osteoarthritis (Majalah Kedokteran Bandung, 2020)
rimary and secondary osteoarthritis relates to inflammatory processes and inflammatory mediators and is destructive to the articular cartilage. Omega-3 is known to be an alternative treatment for rheumatoid arthritis due to the anti-inflammatory effect. This study is an experimental study with simple random sampling using 36 Wistar mice, which were divided into an intervention group and a control group, to understand the effect of omega-3 in slowing progress cartilage destruction in knee joint with osteoarthritis. This study is performed at the Clinical Pharmacology Laboratory, Faculty of Medicine, Universitas Padjadjaran, and the Anatomical Pathology Laboratory, Faculty of Medicine, Universitas Padjadjaran/Dr. Hasan Sadikin General Hospital, in November 2018. Osteoarthritis was induced using intraarticular 1 mg monosodium iodoacetate injection to the mouse knee joint. The intervention group received oral omega-3 every day while the control group did not. Samples from the knee joint were extracted to evaluate the cartilage destruction histopathologically. Results were then analyzed using the Mann-Whitney test and a significant difference of the osteoarthritis grades was identified between the intervention group and the control group on day 7 (p=0.003), day 14 (p=0.003), and day 21 (p=0.003). In addition, a significant difference in the osteoarthritis grading changes was also found between the study group and the control group on day 7 and day 21 (p=0.004). Hence, omega-3 has the ability to slow down the histopathological cartilage destruction progress in mice with knee joint osteoarthritis.Efek Pemberian Omega-3 terhadap Perlambatan Progresivitas Destruksi Kartilago Sendi Lutut Tikus yang Mengalami Osteoartritis Secara HistopatologisOsteoartritis primer dan sekunder berhubungan dengan proses inflamasi dan mediator inflamasi dan merusak tulang rawan artikular. Omega-3 dikenal sebagai pengobatan alternatif untuk rheumatoid arthritis karena efek anti-inflamasi. Penelitian ini adalah penelitian eksperimental dengan pengambilan sampel acak sederhana menggunakan 36 tikus Wistar, yang dibagi menjadi kelompok intervensi dan kelompok kontrol, untuk memahami efek omega-3 dalam memperlambat perkembangan kerusakan tulang rawan pada sendi lutut dengan osteoarthritis. Penelitian ini dilakukan di Laboratorium Farmakologi Klinik, Fakultas Kedokteran, Universitas Padjadjaran, dan Laboratorium Patologi Anatomi, Fakultas Kedokteran Universitas Padjadjaran/Dr. Rumah Sakit Umum Hasan Sadikin Bandung, pada November 2018. Seluruh hewan uji dilakukan induksi osteoartritis dengan monosodium iodoasetat sebanyak 1 mg yang disuntikkan ke dalam sendi lutut. Kelompok perlakuan diberikan omega-3 1 kali per hari per oral, sedangkan kelompok kontrol tidak diberikan omega-3. Sampel jaringan sendi lutut diambil dan dilakukan penilaian destruksi kartilago secara histopatologis. Hasil kemudian dianalisis dengan menggunakan uji Mann-Whitney dan perbedaan yang signifikan dari nilai osteoartritis diidentifikasi antara kelompok intervensi dan kelompok kontrol pada hari 7 (p=0,003), hari 14 (p=0,003), dan hari 21 (p=0,003). Selain itu, perbedaan yang signifikan dalam perubahan penilaian osteoarthritis juga ditemukan antara kelompok studi dan kelompok kontrol pada hari ke 7 dan hari ke 21 (p=0,004). Oleh karena itu, omega-3 memiliki kemampuan untuk memperlambat progres destruksi tulang rawan histopatologis pada tikus dengan osteoartritis sendi lutut.
Keywords: Cartilage destruction; osteoarthritis; omega-3